The implications of Lagoon Beach Hotel (Pty) v Lehane 2016 (3) SA 143 (SCA) for the South African cross-border insolvency dispensation - Boraine, A. (Andre), 1957- (University of Pretoria, 2017)
Mini Dissertation (LLM)--University of Pretoria, 2016.